1990
DOI: 10.1016/0165-1781(90)90155-x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of CT and cognitive measures in normal aging and Alzheimer's disease

Abstract: Abstract. Patients with presumptive Alzheimer's disease (AD) and healthy community volunteers received computed tomographic (CT) brain scans and cognitive tests. The CT scans were quantitatively analyzed with a semiautomated thresholding technique to derive volumetric measures of cerebrospinal fluid (CSF)-to-tissue ratios in six regions of interest (ROIs): lateral ventricles, vertex sulci, frontal sulci, Sylvian fissures, parieto-occipital sulci, and third ventricle. Regression analysis was performed on CT dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 1 publication
1
15
1
Order By: Relevance
“…There was a regional difference for atrophy, with greater promi-nence over the posterior brain regions, both cortically and centrally; in contrast, white-matter changes did not show a regional difference. These findings are consistent with prior reports of atrophy and aging in healthy subjects, 56,57 but extend them with the finding of regional differences. The regional prominence of posterior atrophy with age in healthy subjects is, to our knowledge, a new finding and is particularly intriguing given that Alzheimer disease is commonly associated with atrophy and hypometabolism in posterior regions.…”
Section: Commentsupporting
confidence: 93%
“…There was a regional difference for atrophy, with greater promi-nence over the posterior brain regions, both cortically and centrally; in contrast, white-matter changes did not show a regional difference. These findings are consistent with prior reports of atrophy and aging in healthy subjects, 56,57 but extend them with the finding of regional differences. The regional prominence of posterior atrophy with age in healthy subjects is, to our knowledge, a new finding and is particularly intriguing given that Alzheimer disease is commonly associated with atrophy and hypometabolism in posterior regions.…”
Section: Commentsupporting
confidence: 93%
“…The significant reduction of the thickness of the interthalamic adhesion in geriatric cats in this study suggests the occurrence of atrophy of this structure, which is attributed not only to cell loss, but also to compaction and cell retraction in humans (Turlejski & Djavadian 2012). These findings do not corroborate the results found in humans by some authors (Jernigan et al 2001), however, they are consistent with data reported by most studies, which detected volumetric reduction of the thalamus as advancing age in humans (Pfefferbaum et al 1990, 2013, Walhovd et al 2005, Van der Elst et al 2007, Fjell et al 2009, Walhovd et al 2011.…”
Section: Discussioncontrasting
confidence: 69%
“…These covariates were important elements of the model because previous research has demonstrated that age, education and gender are related to aspects of cognition (Buckner 2004;Coffey et al 2001;Salthouse 1996), and age is also related to gray matter volume Good et al 2001;Lemaitre et al 2005;Murphy et al 1992;Pfefferbaum et al 1990;Raz et al 1997;Salat et al 1999;Thompson et al 2003). That the findings observed here were predominantly frontal does not imply that other areas are not involved.…”
Section: Discussionmentioning
confidence: 50%